Futbolcuların şiddet eğilimlerinin farklı değişkenler açısından incelenmesi - Tuğluk, Mehmet Cem (My University, 2025)
Bu amaç doğrultusunda mevcut çalışmaya, “kolaylıkla bulunabileni örnekleme” yöntemiyle belirlenen toplam 294 futbolcu (263 erkek, 31 kadın) gönüllü olarak katılmıştır. Araştırmada veri toplama aracı olarak; araştırmacı tarafından oluşturulan kişisel bilgi formu ile “Takım Sporları Yapan Sporcularda Şiddet Eğilimi Ölçeği” kullanılmıştır. Veriler için öncelikle normallik varsayımı (çarpıklık-basıklık) incelenmiştir. Verilerin normal dağılıma sahip olduğu belirlendikten sonra parametrik testlerin uygulanması gerektiği sonucuna varılmıştır. Bu bağlamda betimsel istatistikler, bağımsız gruplar için t-testi, tek yönlü varyans analizi (ANOVA) ve gruplar arası farklılıkları belirlemek için Tukey HSD çoklu karşılaştırma testi kullanılmıştır. Ayrıca ölçüm araçlarının Cronbach Alpha iç tutarlık katsayıları hesaplanmıştır. Anlamlılık değeri p<0,05 olarak baz alınmıştır. Bulgular: Elde edilen bulgularda, ortalama değerler futbolcuların şiddet eğilimlerinin düşük olduğunu göstermektedir. Ayrıca futbolcuların cinsiyetlerine göre, sporla ilgilenme yılına göre ve sporculuk durumuna göre benzer şekilde ve düşük düzeyde şiddet eğilimine sahip olduğunu göstermektedir. Braştaki mevkilerine göre, yaş değişkenlerine göre ve milli sporculuk durumuna göre ise anlamlı bir farklılık görülmemiştir. Sonuçlar: Araştırma sonucunda, futbolcuların genel olarak şiddet eğilimlerinin düşük olduğu tespit edilmiştir. Futbolcularda cinsiyet, milli sporculuk durumu, sporla ilgilenme yılı değişkenleri açısından anlamlı farklılıklar görülmemiştir. Ancak öfke durumu olan ile olmayan futbolcular arasında manidar farklılıklar belirlenmiştir.

Objective: To examina the violence tendencies of football players with different variables. Materials and Methods: Based on these thoughts, the aim of the study is to examine the violence tendencies of football players in terms of different variables. In line with this purpose, a total of 294 athletes (263 male, 31 female) determined by the “easily available sampling” method participated voluntarily in the current study. In the study, the personal information form created by the researcher and the “Team Sports Athletes’ Violence Tendency Scale” were used as data collection tools. First of all, the normality assumption (skewness-kurtosis) was examined for the data. After determining that the data had a normal distribution, it was concluded that parametric tests should be applied. In this context, descriptive statistics, t-test for independent groups, one-way analysis of variance (ANOVA) and Tukey HSD multiple comparison test were used to determine the differences between the groups. In addition, Cronbach Alpha internal consistency coefficients of the measurement tools were calculated. The significance value was taken as p<0.05. Results: The average values obtained show that football players have low tendency towards violence. It also shows that football players have a similar and low tendency towards violence according to their gender, years of involvement in sports and status of sportsmanship. No significant difference was observed according to their position in the sport, age variables and status of national sportsmanship. Conclusion: As a result of the research, it was determined that football players generally have low tendency to violence. No significant differences were observed in terms of variables such as gender, national sportsmanship status and years of involvement in sports. However, significant differences were determined between football players with and without anger.
Examination of football players’ violence tendencies in terms of different variables
Keywords: Athlete; Football Player; Futbolcu; Sporcu; Şiddet; Şiddet, Sporda; Turkey; Türkiye; Violence; Violence in sports